Inherently Area‐Selective Atomic Layer Deposition of SiO2 Thin Films to Confer Oxide Versus Nitride Selectivity. (10th June 2021) - Lee, Jinseon; Lee, Jeong‐Min; Oh, Hongjun; Kim, Changhan; Kim, Jiseong; Kim, Dae Hyun; Shong, Bonggeun; Park, Tae Joo; Kim, Woo‐Hee
Abstract: Area‐selective atomic layer deposition (AS‐ALD) offers tremendous advantages in comparison with conventional top‐down patterning processes that atomic‐level selective deposition can achieve in a bottom‐up fashion on pre‐defined areas in multi‐dimensional structures. In this work, a method for exploiting substrate‐dependent selectivity of aminosilane precursors for oxides versus nitrides through chemo‐selective adsorption is reported. For this purpose, AS‐ALD of SiO2 thin films on SiO2 substrates rather than on SiN substrates are investigated. Theoretical screening using density functional theory (DFT) calculations are performed to identify Si precursors that maximize adsorption selectivity; results indicate that di(isopropylamino)silane (DIPAS) has the potential to function as a highly chemo‐selective precursor. Application of this precursor to SiN and SiO2 substrates result in inherent deposition selectivity of ≈4 nm without the aid of surface inhibitors. Furthermore, deposition selectivity is enhanced using an ALD‐etch supercycle in which an etching step inserts periodically after a certain number of ALD SiO2 cycles. Thereby, enlarged deposition selectivity greater than ≈10 nm is successfully achieved on both blanket‐ and SiO2 /SiN‐patterned substrates. Finally, area‐selective SiO2 thin films over 4–5 nm are demonstrated inside 3D nanostructure. This approach for performing inherent AS‐ALD expands the potential utility of bottom‐up nanofabrication techniques for next‐generation nanoelectronic applications. Abstract : Inherent AS‐ALD of SiO2 thin films are demonstrated on SiO2 versus SiN surfaces via chemo‐selective adsorption of an aminosilane precursor. With a combined ASD‐etch strategy, a deposition selectivity >10 nm is successfully achieved on both blanket‐ and SiO2 /SiN‐patterned substrates. This approach represents a new strategy for highly selective deposition that can be incorporated into bottom‐up 3D nanofabrication.